Age of Initial Submarine Volcanism in the Paleo-Tsushima Basin and Implications for Submarine Volcanism in the Opening Stage of the Japan Sea in Northern Kyushu - Ninomiya, Takashi; Shimoyama, Shoichi; Taniguchi, Sho; Takahashi, Toshihiro; Danhara, Tohru; Iwano, Hideki (Geosciences, 2021)
The Tsushima Lapilli Tuff, the thickest tuff in the Taishu Group on Tsushima Island, underwent a thermal event after deposition, and has not previously yielded a reliable age because various ages have been reported. This study clarifies the eruption age and thermal history of the Tsushima Lapilli Tuff based on fission-track (FT) and U–Pb dating of zircon grains using laser ablation inductively coupled plasma mass spectrometry (ICP-LA-MS) and evaluates submarine volcanism during deposition of the Taishu Group in the southwestern Japan Sea, as well as volcanism change on Tsushima Island. This study revealed that thermal events caused rejuvenation in some single-grain FT ages after deposition in the Tsushima Group, and that the eruption age of the Tsushima Lapilli Tuff was 16.2 ± 0.7 Ma; the age of the largest submarine volcanism event in the Taishu Group in Tsushima Island was thus determined. On the basis of our previous studies, this age and tectonism strongly indicate that felsic submarine volcanism occurred between 18 and 16 Ma, accompanied by rapid subsidence, and the volcanism changed from felsic volcanism originating from melting of old continental crust by asthenospheric upwelling to mafic volcanism originating from small-scale lithospheric mantle upwelling from 13.6 Ma onward.